2021
DOI: 10.1038/s41598-021-91383-0
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction strategies of the silver birch (Betula pendula Roth) at post-industrial sites

Abstract: The study aimed to evaluate the parameters of reproductive traits, specimens’ fertility and reproductive efficiency observed in Betula pendula populations growing at different types of sites (zinc-lead heaps, coal mine heaps and unpolluted site). The leaf biomass and the biometric characteristics of inflorescences and fructifications were identified. Moreover, the biometric parameters of B. pendula seedlings were evaluated for examined sites. Seed-originated trees mostly of age 40 were randomly selected and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Birch is one of the species of trees widely distributed in Poland, occurring in various habitat conditions, including on various soil species. Last research has shown that B. pendula has developed traits, which help to survive [ 48 ]. For this reason, it is used as a remedial plant [ 49 51 ], which makes it more and more widespread and conducive to use in biomonitoring [ 1 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Birch is one of the species of trees widely distributed in Poland, occurring in various habitat conditions, including on various soil species. Last research has shown that B. pendula has developed traits, which help to survive [ 48 ]. For this reason, it is used as a remedial plant [ 49 51 ], which makes it more and more widespread and conducive to use in biomonitoring [ 1 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results of dendroclimatological research obtained for birch from the area of Upper Silesia, showing mainly the influence of summer temperatures and drought stress, are slightly different than for pine and oaks, for which the highest dependence on winter temperature was obtained, as well as the second-highest dependence on rainfall conditions in summer [ 32 , 33 ]. On the other hand, it was found that the birches on the heaps are characterised by lower biometric parameters and reproductive abilities than the reference trees [ 34 ]. Additionally, birch trees exposed to heavy metals had leaves that were twice as thick as those of the reference trees ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%